FACTORS INFLUENCING CORPORATE VALUE: THE IMPACT OF LIQUIDITY AND CAPITAL STRUCTURE ON FINANCIAL SECTOR FIRMS LISTED ON THE INDONESIAN STOCK EXCHANGE - Muhammad Afrizal Dema Firmansyah; Syamsul Bahri; Dwi Anggarani (Journal of Public and Business Accounting, 2026)
This study aims to analyze the effect of liquidity and capital structure on firm value in financial sector companies listed on the Indonesia Stock Exchange for the 2022-2024 period. The study used a quantitative approach with secondary data obtained from the companies' financial reports. The sample was selected using a purposive sampling technique, resulting in 79 companies with a total of 237 observations. Data analysis was performed using panel data regression with the help of the EViews 12 application after first selecting a model and testing classical assumptions. The results showed that the most appropriate model was the Fixed Effect Model (FEM). Regression testing showed that one of the other research variables did not show a significant effect. The Adjusted R2 value of 0.789257 indicates that the model is able to explain 78.9% of the variation in firm value, while the remainder is influenced by other factors outside the study. This finding indicates that investor decisions in assessing financial sector companies are influenced not only by liquidity and capital structure but also by various fundamental aspects of the company. The results of this study are expected to provide additional references for the development of research on firm value and provide input for company management in formulating financial policies.